Applications of Biodiesel in Drilling Fluids. (11th March 2021) - Ahmed, Ashraf; Elkatatny, Salaheldin; Al-Afnan, Saad
Abstract : Biodiesel, referred to as the monoalkyl ester of long-chain fatty acid ester that is synthesized by the complete transesterification of triglycerides, has captured the attention of drilling researchers attributing to its magnificent characteristics such as the high flash point, excellent lubricity, nontoxicity, high biodegradability, and abundant feedstock resources, which make it ecofriendly and technically and economically feasible for a sustainable drilling operation. There are several studies that reported and documented the usage of biodiesel in drilling fluids on laboratory and field scales. In this paper, the production and the key physical and chemical properties of biodiesel are thoroughly reviewed. Moreover, the applications of biodiesel in drilling muds either as base fluids or additives were comprehensively surveyed. The literature review revealed that the challenges of biodiesel applications in drilling mud systems are related to its chemical reactivity and adverse interactions with some additives, along with its performance deficiency at temperature above 120°C. Therefore, further investigation on temperature stability and additive compatibility is recommended. In addition, as a new approach, it is recommended to study the potentiality of using crude waste oils in drilling mud formulations. The lessons learned and recommendations stated in this paper will assist in enhancing the proved use of biodiesel and drilling fluid optimization.